Home: made with plants - an exhibition co-creation process with migrant domestic workers - Leong, Man Wei (Nanyang Technological University, 2022)
Home: Made with Plants explores the process of co-creating exhibitions on ethnobotany in Singapore. Using community-based research and participatory design, it engages migrant domestic workers (MDWs) with personal connections and deep knowledge on plants in Southeast Asia to share and curate stories of using plants in the home. Stemming from the experience of exhibition-making at the Centre for Ethnobotany at the Singapore Botanic Gardens, this project attempts to formalise a methodology for co-creating exhibitions and activating public spaces and gardens. The exhibition co-creation journey is organised into a publication documenting real community engagements to facilitate future users. Home: Made with Plants aims to rediscover our relationships with the plants and people in and around our homes. It promotes the idea of harvesting polyvocal contributions in ethnobotany to meaningfully grow our communities together.